Comparison of untwist mechanics before and after surgery for multiple ventricular septal defects in infants using two-dimensional speckle-tracking echo cardiography - Yoshiko ONUMA; Kazuyoshi SAITO; Sayaka OZAWA; Keiichi HIRONO; Fukiko ICHIDA (TOYAMA MEDICAL JOURNAL, 2018)
[Abstract] The LV torsion and untwisting velocity was evaluated using two-dimensional speckle-tracking imaging (2D-STE), in infants with mVSDs before and after surgery. Methods: The study included 36 infants with mVSDs (Group A, preoperative patients; Group B-1, patients within 2 months of the operation; Group B-2, patients 2-4 months after the operation) and 16 healthy control infants. The LV torsion and untwist were normalized by LV length and defined as torsion N (TN), and the peak untwisting velocity/torsion N (UTN). Results: No significant differences were noted among the four groups for LV ejection fraction (EF) or the Tei index. The diastolic index E/e' and UTN were significantly higher in Group A than in the control group, and significantly decreased in Groups B-1 and B-2. Excluding B-1 patients, E/e' and UTN tended to correlate (r=-0.618; p<0.0001). Conclusion: The present study was the first to reveal that elevated UTN is associated with increased E/e' under preserved LV systolic function, presumably compensating diastolic capacity for increased preload due to the VSD shunt. 2D-STE facilitates the serial evaluation of the LV torsional behavior and its physiological implications in clinical settings, even in infants with rapid heart rates.